"Thinstagram": Image content and observer body satisfaction influence the when and where of eye movements during instagram image viewing. (January 2023) - Scott, Graham G.; Pinkosova, Zuzana; Jardine, Eva; Hand, Christopher J.
Abstract: Selective Exposure Theory (Aruguete & Calvo, 2018; Bigné et al., 2020) suggests that on social media, viewers pay most attention to content which aligns with their values and preferences. Individuals engage in self-assessment by comparing themselves to others (Social comparison theory: Festinger, 1954). We predicted that the characteristics of Instagram arrays and participants' own body satisfaction would combine to influence their visual processing of computer-based images. A 3 (Body Shape: Underweight, Average, Overweight) × 2 (Body Part: Face-only; Body-only) repeated measures design was used. We recruited 60 (young) women to view arrays of images as displayed on Instagram [ M age  = 20.75 years, SD age  = 2.74 years]. A separate, naïve group of 37 participants rated 165 stimulus images on a scale of under-to-over-weight. These normed images were used to create artificial, ecologically-valid 3 × 4 Instagram image arrays containing two of each type of stimulus image. We recorded participants' eye movements with a high degree of spatial and temporal resolution while participants freely engaged with these arrays. We then collected participants' body satisfaction data (Slade et al., 1990). Results demonstrated inter-relationships between eye movement behaviour and Body Shape, Body Part, and body satisfaction. In short, both bottom-up stimulus characteristics and top-down satisfaction impacted measures of processing. Image content was particularly relevant to 'when' measures of processing time, whereas body satisfaction was more-influential upon 'where' measurements (fixations counts, number of visits per stimulus image). Our study is the first of its kind to show such effects. Future research is needed to understand such effects in clinical and/or non-female users of Instagram and other platforms. Highlights: Bottom-up and top-down factors had differential effects on 'where' and 'when' eye movement measures. Participants selectively attended to bodies vs. faces, and underweight and average vs. overweight images. Participants avoided looking at images which reflected their own areas of lower body satisfaction.